Improving and diversifying planted forages through selection, breeding and inclusion in local production systems - Examples of South-South learning - Peters, Michael; Mwendia, Solomon W.; Castiblanco, Valheria; Hoek, Rein van der; Burkart, Stefan; Douxchamps, Sabine; Ohmstedt, Uwe; Notenbaert, An Maria Omer (Wageningen University & Research, 2021)
Livestock based systems provide livelihoods to 1 billion people and account for 40% of global agricultural gross domestic product. Animal-source foods provide 14% of the calories and 33% of the proteins consumed globally and provide essential micronutrients, such as vitamin A, B-12, riboflavin, calcium, iron and zinc. In addition, livestock has high cultural and social values. Producing feed for livestock uses about 84% of the world’s agricultural land (Erb et al. 2007; Foley et al. 2011). The share is even higher in developing countries (FAO 2009). Producing enough animal feed is a challenge, especially in ruminant systems, accounting for 50 to 60% of the total production costs (Swanepoel et al. 2010). Land resources that can be used for feed production are increasingly constrained.